Membangun Kreativitas Dan Kesadaran Lingkungan Melalui Lomba Daur Kreatif Menggunakan Sampah Di SMAN 2 Narmada: Daur Kreatif - Samarina, Sisi; Nisa, Saskia Hairun; Saputri, Olifia Riski; Sultania, Tri; Wulandari, Alda; Liyyin, Sania; Hultaria, Ela; Redjeki, Suci Insani; Sundari, Siti; Atmawijaya, Rianto; Wahyudi, Lalu Trisna; Mayadi, Muhamad (Universitas Mataram, 2025)
The aim of this program is to increase students' creativity in utilizing used goods into valuable works while at the same time instilling environmental awareness at SMAN 2 Narmada by utilizing used goods. This research uses a descriptive qualitative approach. This approach was chosen because the aim of the research was not to test certain hypotheses or speculation, but rather to obtain in-depth understanding and interpretation. The results of this program are high enthusiasm and the ability to work together in teams, producing innovative works that are not only creative but also functional. This program has also succeeded in raising environmental awareness among students and honing their practical skills in managing used goods.